Superficial, Profound, and Reflective-Critical Reading Comprehension of a Eementary Student - Rivera Suárez, Ilma Yaneth (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper presents partial results of an investigation aimed to describe and analyze how students of Escuela Nueva, in a Colombian elementary, understand superficial, profound, critical, and reflective expository texts, with cold and warm help from the teacher and support from parents. The interpretive paradigm was used with a qualitative approach, using educational ethnography. The sample consisted of seven primary school children. I used surveys and the application of multidisciplinary guides, in which, based on expository texts, I questioned the students for mobilizing comprehensive processes. For this article, the results show the understanding of an expository text of a student in the fifth grade. For superficial understanding, the student retrieved literal information using loose words, short sentences, and extensive textual statements; in the profound, he saw hidden senses and associated the readings with their socio-cultural context; in reflective-critical took reasoned positions. The cognitive and affective aids of the teacher and involvement of parents contributed to the consolidation of knowledge